All-solid-state battery with high energy density and method for manufacturing the same

By adjusting the size and layout of the solid electrolyte layer, the problems of low energy density and short-circuiting of the electrode edges are solved, and an all-solid-state battery with high energy density and stability are realized, and the manufacturing process is simplified.

CN111987365BActive Publication Date: 2024-12-13HYUNDAI MOTOR CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN201910983341.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-05-23
Filing Date
2019-10-16
Publication Date
2024-12-13
Estimated Expiration
2039-10-16

AI Technical Summary

Technical Problem

The actual energy density and output of all-solid state batteries are lower than that of lithium-ion batteries using liquid electrolytes, and there is a problem of short circuit at the edge of the electrode.

Method used

By adjusting the size and arrangement of the solid electrolyte layer, it ensures that its area is larger than that of the electrode unit, and reduces the number of current collectors during the manufacturing process, meets specific edge distances and thickness relationships, prevents electrode edge short circuits, and simplifies the manufacturing process.

Benefits of technology

A fully solid state battery with high energy density and high stability is achieved, which simplifies the manufacturing process, reduces the number of current collectors, and increases the energy density per unit volume and per unit weight of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111987365B_ABST
    Figure CN111987365B_ABST
Patent Text Reader

Abstract

The present invention relates to an all-solid-state battery with high energy density and a method for manufacturing the same. In manufacturing the all-solid-state battery, the battery assembly is pressurized instead of each battery cell, and the structure of the battery is simplified by using a reduced number of first electrode collectors and second electrode collectors. In particular, the all-solid-state battery includes: a first cell, each cell including a first electrode collector and a first electrode active material layer disposed on each opposing surface of the first electrode collector; a second cell, each cell including a second electrode collector and a second electrode active material layer disposed on each opposing surface of the second electrode collector; and a solid electrolyte layer disposed between the corresponding first cell and the corresponding second cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an all-solid-state battery having high energy density and a method for manufacturing the same. Background Art

[0002] The statements in this section merely provide background information related to the present disclosure and may not constitute prior art.

[0003] Rechargeable secondary batteries are used not only for small electronic devices such as mobile phones and laptop computers, but also for large motor vehicles such as hybrid vehicles and electric vehicles. Therefore, it is desirable to develop secondary batteries with high stability and high energy density.

[0004] Secondary batteries in the prior art are mainly based on organic solvents (organic liquid electrolytes) to form batteries, so secondary batteries have limitations in improving stability and energy density.

[0005] All-solid-state batteries using inorganic solid electrolytes are based on technology that excludes organic solvents, and therefore, in recent years, all-solid-state batteries have attracted attention because the batteries can be manufactured safely in a simple form.

[0006] However, we found that all-solid-state batteries have limitations, namely, their actual energy density and output may not reach those of lithium-ion batteries using liquid electrolytes. All-solid-state batteries have an electrolyte membrane including a solid electrolyte between the positive and negative electrodes, so they are large and bulky compared to lithium-ion batteries in the prior art. Therefore, all-solid-state batteries have low energy per unit volume and low energy density per unit weight. When the electrolyte membrane is made thin to prevent this, a short circuit may occur between the positive and negative electrodes.

[0007] Therefore, it is desirable to simplify the process of manufacturing an all-solid-state battery and develop an all-solid-state battery with high stability and energy density. Summary of the invention

[0008] The present disclosure provides an all-solid-state battery that exhibits the original functions of a rechargeable secondary battery while having high stability and high energy density.

[0009] Another object of the present disclosure is to provide a method for efficiently manufacturing an all-solid-state battery, which is a method for suppressing or preventing electrode edge short-circuiting through a simple process such as adjusting the size of a solid electrolyte layer.

[0010] The purpose of the present disclosure is not limited to the above-mentioned purpose. These and other purposes of the present disclosure can be understood from the following detailed description, and will become more obvious from the form of the present disclosure. Moreover, the purpose of the present disclosure can be achieved by the means and combinations thereof shown in the attached claims.

[0011] In one form of the present disclosure, an all-solid-state battery includes: a plurality of first units, each of which includes a first electrode collector and a first electrode active material layer disposed on each relative surface of the first electrode collector; and a plurality of second units, each of which includes a second electrode collector and a second electrode active material layer disposed on each relative surface of the second electrode collector. The first units of the plurality of first units and the second units of the plurality of second units are stacked alternately with each other. One of the plurality of solid electrolyte layers is disposed between a corresponding first unit among the plurality of first units and a corresponding second unit among the plurality of second units. Each of the plurality of solid electrolyte layers has an area greater than that of each of the first units and equal to or greater than that of each of the second units.

[0012] The corresponding first cell may have an area equal to or larger than that of the corresponding second cell.

[0013] One of the corresponding first unit and the second unit can be located on one surface of the solid electrolyte layer, and the remaining one of the corresponding first unit and the second unit, which is different from the unit located on one surface, is located on the opposite surface of the solid electrolyte layer, so that the first electrode active material layer and the second electrode active material layer are stacked to contact the solid electrolyte layer.

[0014] The central portion of the solid electrolyte layer may have an area equal to or larger than that of the corresponding first unit or the corresponding second unit.

[0015] All-solid-state batteries can satisfy the following equation 1 or equation 2:

[0016] Equation 1:

[0017] 2 <log(x 1 y)<6,

[0018] Equation 2:

[0019] 2 <log(x 2 y)<6,

[0020] Among them, x 1 is the distance between the edge of the solid electrolyte layer and the edge of the first unit, x 2 is the distance between the edge of the solid electrolyte layer and the edge of the second unit, and y is the thickness of the solid electrolyte layer.

[0021] The thickness (y) of the solid electrolyte layer may be approximately 10 μm to 500 μm.

[0022] The distance (x 1 ) or the distance between the edge of the solid electrolyte layer and the edge of the corresponding second unit (x 2) can be about 10μm to 2000μm.

[0023] An edge of the solid electrolyte layer and an edge of the corresponding first unit may be parallel to each other, and

[0024] An edge of the solid electrolyte layer and an edge of the corresponding second unit may be parallel to each other.

[0025] In one form, the first electrode current collector corresponding to the first unit has a thickness of about 4 μm to 20 μm, and is disposed between a pair of first electrode active material layers corresponding to the first unit.

[0026] In another form, the second electrode current collector corresponding to the second unit has a thickness of about 5 μm to 20 μm, and is disposed between a pair of second electrode active material layers corresponding to the second unit.

[0027] The first electrode active material layer may have a thickness of about 50 μm to 300 μm, a composite density of about 1.2 g / cc to 3.5 g / cc, and a density of about 10 mg / cm 2 Up to 45mg / cm 2 load level, and a brightness index of approximately 30 to 80.

[0028] The second electrode active material layer may have a thickness of about 50 μm to 300 μm, a composite density of about 2.5 g / cc to 5.0 g / cc, and a 2 Up to 35mg / cm 2 load level, and a brightness index of approximately 40 to 90.

[0029] In another form of the present disclosure, a method for manufacturing an all-solid-state battery includes the following steps: preparing a plurality of first units, each of which includes a first electrode current collector and a first electrode active material layer disposed on each relative surface of the first electrode current collector; preparing a plurality of second units, each of which includes a second electrode current collector and a second electrode active material layer disposed on each relative surface of the second electrode current collector; preparing a battery assembly by alternately stacking first units in the plurality of first units and second units in the plurality of second units with each other; and pressurizing the battery assembly. The preparation of the battery assembly also includes: disposing a solid electrolyte layer between a first unit of the first unit and a second unit of the second unit, wherein the solid electrolyte layer has a release film on its first surface. The solid electrolyte layer has an area greater than each of the first unit and the second unit.

[0030] The step of setting a solid electrolyte layer between the first unit and the second unit may include: stacking one of the first unit and the second unit on the second surface of the solid electrolyte layer to which a release film is not attached; removing the release film from the first surface of the solid electrolyte layer; and stacking the remaining units of the first unit and the second unit on the first surface from which the release film is removed.

[0031] The method may further include: arranging the solid electrolyte layer, the first unit, and the second unit to satisfy the following Equation 1 or Equation 2:

[0032] Equation 1:

[0033] 2 <log(x 1 y)<6,

[0034] Equation 2:

[0035] 2 <log(x 2 y)<6,

[0036] Among them, x 1 is the distance between the edge of the solid electrolyte layer and the edge of the first unit, x 2 is the distance between the edge of the solid electrolyte layer and the edge of the second unit, and y is the thickness of the solid electrolyte layer.

[0037] The thickness (y) of the solid electrolyte layer is about 10 μm to 500 μm.

[0038] The distance between the edge of the solid electrolyte layer and the edge of the first unit (x 1 ) or the distance between the edge of the solid electrolyte layer and the edge of the second unit (x 2 ) is approximately 10μm to 2000μm.

[0039] An edge of the solid electrolyte layer and an edge of the first unit may be parallel to each other, and

[0040] An edge of the solid electrolyte layer and an edge of the second unit may be parallel to each other.

[0041] When preparing the first unit and the second unit, the first unit and the second unit may not be pressurized.

[0042] The pressurization may be performed at about 250 MPa to 500 MPa.

[0043] According to the present disclosure, compared with the manufacturing process in the related art (in the prior art, basic battery cells are pressurized separately and then stacked on each other), the manufacturing process can be simplified because a battery assembly stacking two or more cells is prepared and pressurized.

[0044] In addition, compared with the battery assembly of the prior art (in which two or two basic battery cells are stacked, each cell including a current collector, an electrode and a solid electrolyte layer), an all-solid-state battery according to one form of the present disclosure is configured so that the battery cells configured with electrodes are stacked on the opposite surfaces of the current collector, thereby reducing the number of current collectors used, thereby obtaining an all-solid-state battery with a high energy density.

[0045] In addition, according to the present disclosure, there is provided a solid electrolyte layer having a thickness within a predetermined range and having a larger area than each of the first unit cell and the second unit cell, and thus short circuiting of electrode edges can be prevented.

[0046] The effects of the present disclosure are not limited to the above-mentioned effects, and the present disclosure includes all effects that can be derived from the detailed description.

[0047] Further areas of applicability will become apparent from the description provided herein.It should be understood that the description and specific examples are intended for purposes of illustration only and are not intended to limit the scope of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] In order to make the present disclosure easier to understand, various forms of the present disclosure will now be described by way of example with reference to the accompanying drawings, in which:

[0049] Figure 1 is a schematic diagram showing an all-solid-state battery;

[0050] Figure 2 is a schematic diagram showing a first unit;

[0051] Figure 3 is a schematic diagram showing a second unit;

[0052] Figure 4 is a schematic diagram showing a central portion of a solid electrolyte layer;

[0053] Figure 5 is a flow chart showing a method of manufacturing an all-solid-state battery;

[0054] Fig. 6A It means 2<log(x 1 Photos showing whether the edges of the electrodes of the all-solid-state battery outside the range of y) < 6 are protected;

[0055] Figure 6B It means that 2<log(x 1 Photos showing whether the edges of the electrodes of the all-solid-state battery in the range of y) < 6 are protected;

[0056] Fig. 7Ais a photograph of an interface of an intermediate layer between a second stacking unit and a third stacking unit of an all-solid-state battery after the battery assembly is pressurized to 200 MPa; and

[0057] Figure 7B is a photograph of the interface of the intermediate layer between the second stacking unit and the third stacking unit of the all-solid-state battery after the battery assembly was pressurized to 300 MPa.

[0058] The drawings herein are for illustration purposes only and are not intended to limit the scope of the present disclosure in any way. DETAILED DESCRIPTION

[0059] The following description is merely exemplary in nature and is not intended to limit the present disclosure, application, or uses. It should be understood that throughout the drawings, corresponding reference numerals indicate the same or corresponding components and features.

[0060] The above and other purposes, features and advantages of the present disclosure will be more clearly understood according to the following exemplary forms when combined with the accompanying drawings. The forms of the present disclosure are proposed to fully disclose the present disclosure and help those of ordinary skill in the art to best understand the present disclosure. Various changes can be made to the following forms, and the scope of the present disclosure is not limited to the following forms.

[0061] In these drawings, for the sake of clarity and convenience of description, the shape and size of the components may be enlarged. It will be understood that, although the terms first, second, etc. can be used here to describe various elements, these elements should not be limited by these terms. These terms are only used to distinguish one element from another element. For example, without departing from the teaching of the present disclosure, the first element discussed below can be referred to as the second element. Similarly, the second element can also be referred to as the first element. An element represented in the singular form in this specification can be a plurality of elements, unless it must be singular in context.

[0062] It will be further understood that the terms "comprising", "including", "having", etc., when used in this specification, specify the presence of features, integers, steps, operations, elements, components and / or combinations thereof, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof. In addition, it will be understood that when a layer, film, region or plate is referred to as being "on" or "under" another layer, another film, another region or another plate, it may be also "directly" or "indirectly" present on another layer, film, region, plate or one or more intermediate layers.

[0063] Unless otherwise stated, all numerals, values ​​and / or expressions used in this article relating to the quantity of ingredients, reaction conditions, polymer compositions and formulations should be understood to be modified in all cases by the term "about", because such numerals are essentially approximate values, which, among other things, reflect the various measurement uncertainties encountered when obtaining such values. In addition, in the case of numerical ranges disclosed herein, the range is continuous and, unless otherwise stated, includes each value from the minimum value to the maximum value of the range. Further, unless otherwise stated, the range refers to integers, including each integer from the minimum value to the maximum value (including the maximum value).

[0064] Figure 1 is a schematic diagram showing an all-solid-state battery 1 according to one form of the present disclosure. Figure 1 , the all-solid-state battery 1 includes: a first unit 10; a second unit 20; and a solid electrolyte layer 30 disposed between one first unit 10 and one second unit 20. Hereinafter, for ease of explanation, the all-solid-state battery 1 will be described based on one first unit 10, one second unit 20, and one solid electrolyte layer 30.

[0065] In the first electrode current collector and the second electrode current collector included in the all-solid-state battery, the first electrode and the second electrode may be positive electrodes or negative electrodes, respectively.

[0066] In one form, the polarities of the first electrode and the second electrode are different from each other. For example, in the case where the first electrode is positive, the second electrode can be negative. Alternatively, in the case where the first electrode is negative, the second electrode can be positive. In another form, the first electrode can be negative and the second electrode can be positive.

[0067] Unit 1

[0068] Figure 2 is a schematic diagram showing a first unit 10 in one form of the present disclosure. Figure 2 , the first unit 10 includes: a first electrode current collector 11; and a first electrode active material layer 12 disposed on opposite surfaces of the first electrode current collector 11. In addition, the first unit may have an area equal to or larger than that of the second unit.

[0069] The first electrode may be a positive electrode or a negative electrode. In the case where the first electrode is a negative electrode, the second electrode may be a positive electrode. Alternatively, in the case where the first electrode is a positive electrode, the second electrode may be a negative electrode. However, the polarity of the first electrode and the second electrode is not particularly limited. In one form, the first electrode may be a negative electrode.

[0070] There is no particular limitation on the first electrode current collector 11 as long as the first electrode current collector 11 is conductive and has a current collecting function. The material of the first electrode current collector 11 may include one selected from the group consisting of copper (Cu), copper (Cu) coated with carbon (C), and nickel (Ni). For example, the first electrode current collector 11 may be in the shape of a nickel mesh, a copper foil, etc.

[0071] The first electrode current collector 11 may have a thickness of about 4 to 20 μm. For example, copper (Cu) may have a thickness of about 5 to 15 μm, copper (Cu) coated with carbon (C) may have a thickness of about 7 to 20 μm, or nickel (Ni) may have a thickness of about 4 to 20 μm.

[0072] The first electrode active material layer 12 may include a first electrode active material, a solid electrolyte, a conductive additive, a binder, and the like.

[0073] The first electrode active material may be a carbon material such as natural graphite, artificial graphite, graphite carbon fiber, resin sintered carbon, or an alloy material mixed with a solid electrolyte. Examples of alloy materials may include lithium alloys (e.g., LiAl, LiZn, Li 3 Bi, Li 3 Cd, Li 3 Sb、Li 4 Si、Li 4.4 Pb、Li 4.4 Sn、Li 0.17 C and LiC 6 ), or metal oxides (such as lithium titanate (Li 4 Ti 5 O 12 ) and Zn).

[0074] The function of the solid electrolyte is to allow lithium ions to be transported in the first electrode active material layer 12. The solid electrolyte may be an oxide-based solid electrolyte or a sulfide-based solid electrolyte. However, in another form, a sulfide-based solid electrolyte having high lithium ion conductivity may be used.

[0075] Sulfide-based solid electrolytes can be: Li 2 SP 2 S 5 , Li 2 SP 2 S 5 -LiI, Li 2 SP 2 S 5 -LiCl, Li 2 SP 2 S 5 -LiBr, Li2 SP 2 S 5 -Li 2 O. Li 2 SP 2 S 5 -Li 2 O-LiI、Li 2 S-SiS 2 , Li 2 S-SiS 2 -LiI, Li 2 S-SiS 2 -LiB, Li 2 S-SiS 2 -LiC l , Li 2 S-SiS 2 -B 2 S 3 -LiI, Li 2 S-SiS 2 -P 2 S 5 -LiI, Li 2 SB 2 S 3 , Li 2 SP 2 S 5 -ZmSn (where m and n are positive numbers, Z is one of Ge, Zn and Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -LixMOy (where x and y are positive numbers, M is one of P, Si, Ge, B, Al, Ga and In), Li 10 G 2 S1 2 wait.

[0076] The sulfide-based solid electrolyte may have an average particle size (D50) of about 0.1 μm to 10 μm.

[0077] In one form, a lithium ion conductivity of about 1x10 -4 S / cm or higher sulfide-based solid electrolytes.

[0078] The conductive additive may be carbon black, conductive graphite, ethylene black, graphene, or the like.

[0079] The first electrode active material layer 12 may include a binder. The binder material may be butadiene rubber (BR), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC), etc., but is not limited thereto.

[0080] The first electrode active material layer 12 may have a thickness of about 50 μm to 300 μm. The first electrode active material layer 12 may have a composite density of about 0.1 g / cc to 2.0 g / cc before pressurization, and may have a composite density of about 1.2 g / cc to 3.5 g / cc after pressurization. The first electrode active material layer 12 may have a composite density of about 10 mg / cm 2 Up to 45mg / cm 2 load level and a brightness index of approximately 30 to 80.

[0081] The term "loading level" used herein means the loading amount of the material constituting the first electrode active material layer.

[0082] When each battery cell including a negative electrode, a positive electrode and a solid electrolyte is stacked on each other as in the process in the related art, the first electrode collectors are stacked on each other or the second electrode collectors are stacked on each other so that the two collectors are stacked on each other. Therefore, the battery cell stack in the prior art has the following problem: many collectors are used, so that its energy density is low. On the other hand, according to one form of the present invention, a first electrode collector 11 is arranged between a pair of first electrode active material layers 12. Therefore, compared with the prior art, the number of first electrode collectors is reduced. As a result, the process of manufacturing an all-solid-state battery can be simplified, and an all-solid-state battery with a high energy density can be obtained.

[0083] Unit 2

[0084] Figure 3 is a schematic diagram showing a second unit 20 in one form of the present disclosure. Figure 3 , the second unit 20 includes: a second electrode current collector 21; and a second electrode active material layer 22 disposed on opposite surfaces of the second electrode current collector 21. In addition, the second unit may have an area equal to or smaller than that of the first unit.

[0085] The second electrode may be a positive electrode or a negative electrode. In the case where the second electrode is a positive electrode, the first electrode may be a negative electrode. Alternatively, in the case where the second electrode is a negative electrode, the first electrode may be a positive electrode. However, the polarity of the first electrode and the second electrode is not particularly limited. In one form, the second electrode may be a positive electrode.

[0086] The second electrode current collector 21 is not particularly limited as long as the second electrode current collector 21 is conductive and has a current collecting function.

[0087] The material of the second electrode current collector 21 may include aluminum (Al) or aluminum (Al) coated with carbon (C). For example, the second electrode current collector 21 may be in the shape of an aluminum foil or the like.

[0088] The second electrode current collector 21 may have a thickness of about 5 to 20 μm. For example, the thickness of aluminum (Al) may be about 5 to 15 μm, or the thickness of aluminum (Al) coated with carbon (C) may be about 7 to 20 μm.

[0089] The second electrode active material layer 22 may include a second electrode active material, a solid electrolyte, a conductive additive, a binder, and the like.

[0090] The second electrode active material may be an oxide active material or a sulfide active material.

[0091] The oxide active material can be a rock salt layered active material, such as LiCoO 2 , LiMnO 2 , LiNiO 2 , LiVO 2 and Li 1+x Ni 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 ; Spinel active materials, such as LiMn 2 O 4 , Li(Ni 0.5 Mn 1.5 ) 4 ; Inverse spinel active materials, such as LiNiVO 4 and LiCoVO 4 ; Olivine active materials, such as LiFePO 4 , LiMnPO 4 , LiCoPO 4 and LiNiPO 4 ; Silicon-containing active materials, such as Li 2 FeSiO 4 and Li 2 MnSiO 4 ; Lithium salt layered active materials, such as LiNi 0.8 Co (0.2-x) Al x O 2 (0<x<0.2), in which some transition metals are replaced by foreign metals; spinel active materials, such as Li 1+x Mn 2-x-y My O 4 (wherein M is at least one selected from Al, Mg, Co, Fe, Ni and Zn, 0<x+y<2), wherein some transition metals are replaced by heterogeneous metals; or lithium titanate, such as Li 4 Ti 5 O 12 .

[0092] The sulfide active material may be copper phyllox compounds, iron sulfide, cobalt sulfide, nickel sulfide, and the like.

[0093] The solid electrolyte may be an oxide-based solid electrolyte or a sulfide-based solid electrolyte. The solid electrolyte may be the same as or different from the solid electrolyte contained in the first electrode active material layer 12.

[0094] The conductive additive may be carbon black, conductive graphite, ethylene black, graphene, or the like.

[0095] The material of the binder may be butadiene rubber (BR), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC), etc. The material of the binder may be the same as or different from the binder included in the first electrode active material layer 12 .

[0096] The second electrode active material layer 22 may have a thickness of about 50 μm to 300 μm. The second electrode active material layer 22 may have a composite density of about 0.5 g / cc to 3.0 g / cc before pressurization, and may have a composite density of about 2.5 g / cc to 5.0 g / cc after pressurization. The second electrode active material layer 22 may have a density of about 10 mg / cm 2 Up to 35mg / cm 2 load level and a brightness index of approximately 40 to 90.

[0097] One second electrode current collector 21 is disposed between a pair of second electrode active material layers 22. Therefore, as with the first electrode current collector 11, the number of second electrode current collectors is reduced compared to the battery cell stack in the prior art. As a result, the process of manufacturing an all-solid-state battery can be simplified, and an all-solid-state battery with high energy density can be obtained.

[0098] Solid electrolyte layer

[0099] The solid electrolyte layer 30 of one form of the present invention is disposed between the first unit and the second unit to allow lithium ions to move between the positive electrode and the negative electrode. Figure 1 and Figure 4, one of the first unit and the second unit is located on one surface of the solid electrolyte layer, and the remaining units of the first unit and the second unit that are different from the units located on one surface are located on the opposite surface of the solid electrolyte. Therefore, the first electrode active material layer and the second electrode active material layer are stacked in contact with the solid electrolyte layer.

[0100] In one form of the present disclosure, reference Figure 4 , x 1 is the distance between the edge of the solid electrolyte layer and the edge of the first unit, x 2 is the distance between the edge of the solid electrolyte layer and the edge of the second unit, and y is the thickness of the solid electrolyte layer. The edge of the solid electrolyte layer and the edge of the first unit may be parallel to each other, and the edge of the solid electrolyte layer and the edge of the second unit may be parallel to each other.

[0101] Here, the distance x between the edge of the solid electrolyte layer and the edge of the first unit is 1 or the distance x between the edge of the solid electrolyte layer and the edge of the second unit 2 It may be about 10 μm to 2000 μm and the thickness y of the solid electrolyte layer may be about 10 μm to 500 μm. In one form, the equation 1 may be satisfied: 2<log(x 1 y)<6, or equation 2: 2<log(x 2 y)<6. When log(x 1 y) or log(x 2 When the value of log(x) is less than 2, the possibility of short circuit is high because the edge of the electrode may be exposed after the pressing process. 1 y) or log(x 2 When the value of y) is greater than 6, the energy density may be reduced due to providing an unnecessary amount of material in the all-solid-state battery.

[0102] The solid electrolyte layer 30 may include an oxide-based solid electrolyte layer or a sulfide-based solid electrolyte contained in the second electrode active material layer 22. Here, the solid electrolyte may be the same as or different from the solid electrolyte contained in the first electrode active material layer 12. Figure 5 is a flowchart showing a method of manufacturing an all-solid-state battery 1 according to another form of the present disclosure. Figure 5The method for manufacturing an all-solid-state battery 1 includes the following steps: preparing a first unit including a first electrode collector 11 and a first electrode active material layer 12 (S10); preparing a second unit including a second electrode collector 21 and a second electrode active material layer 22 (S20); preparing a solid electrolyte layer having a release film attached to one surface thereof (S30); alternately stacking the first unit 10 and the second unit 20, and disposing the solid electrolyte layer between the first unit and the second unit to prepare a battery assembly (S40); and pressurizing the battery assembly (S50).

[0103] When preparing the first unit (S10), the first electrode active material layer 12 is arranged on the opposite surface of the first electrode current collector 11. The manner of arranging the first electrode active material layer 12 on the opposite surface of the first electrode current collector 11 is not particularly limited. For example, the manner of disposing the first electrode active material layer 12 on the opposite surface of the first electrode current collector 11 may be: slurry coating process, sandblasting, aerosol deposition, cold spraying, sputtering, vapor growth, thermal spraying, etc. In another form, a slurry coating process may be performed.

[0104] The slurry coating process may be performed by preparing a slurry containing a first electrode active material, coating the opposite surface of the first electrode current collector 11 with the prepared slurry, and drying the slurry. The process of coating the first electrode current collector with the slurry may be performed by dam type slurry coating, doctor blade, gravure transfer, reverse roll coating, die coating, etc.

[0105] The slurry including the first electrode active material may be prepared by mixing the first electrode active material and a solvent and optionally a solid electrolyte and a binder according to a known method in the art.

[0106] The solvent for preparing the slurry is not particularly limited, as long as the solvent does not adversely affect the performance of the first electrode active material. Examples of solvents include hydrocarbon-based organic solvents, such as heptane, toluene and hexane. In one form, a hydrocarbon-based organic solvent obtained by a dehydration process with a reduced water content can be used. The first electrode active material, solid electrolyte and binder that can be included in the slurry (the slurry includes the first electrode active material) can be the above-mentioned materials that can be included in the first electrode active material layer 12.

[0107] In the preparation of the second unit ( S20 ), the second electrode active material layer 22 is provided on the opposite surface of the second electrode current collector 21 .

[0108] The second electrode active material layer 22 may be arranged on the opposite surface of the second electrode current collector 21 in the same manner as the first electrode active material layer 12 is provided on the first electrode current collector 12, or a metal material capable of lithium oxidation and reduction may be prepared on the opposite surface of the second electrode current collector 21. The metal material may include lithium (Li) or indium (Id).

[0109] When preparing the solid electrolyte layer ( S30 ), the solid electrolyte layer 30 is prepared by attaching a release film to one surface thereof.

[0110] The surface of the solid electrolyte layer to which the release film is attached (hereinafter referred to as the first surface) may not be limited. When the solid electrolyte layer is arranged between the first unit and the second unit, the first unit or the second unit may be stacked on the opposite surface (hereinafter referred to as the second surface) to which the release film is not attached.

[0111] The thickness of the solid electrolyte layer 30 may be selected based on the desired battery characteristics. The thickness of the solid electrolyte layer 30 may be within a range that reduces or minimizes a short circuit between the first electrode active material layer 12 and the second electrode active material layer 22. In one form, the thickness y of the solid electrolyte layer may be from about 10 μm to 500 μm. When the thickness of the solid electrolyte layer is less than about 10 μm, there is a high likelihood of a short circuit occurring because the edges of the electrodes may be exposed. When the thickness of the solid electrolyte layer is greater than about 500 μm, the solid electrolyte may rupture or occupy a larger space due to a high expansion rate in a planar direction, thereby reducing energy density. As follows, when the thickness of the solid electrolyte layer satisfies Equation 1:2 <log(x 1 y)<6 or equation 2:2 <log(x 2 When y)<6, the edge short circuit of the electrode can be prevented, and an all-solid-state battery with high energy density can be obtained.

[0112] The solid electrolyte layer 30 includes a solid electrolyte and may include a binder as needed. The material of the solid electrolyte that may be included in the second electrode active material layer 22 may be used as the material of the solid electrolyte layer. When the second electrode active material layer 22 includes a solid electrolyte, the solid electrolyte included in the solid electrolyte layer 30 and the solid electrolyte included in the second electrode active material layer 22 may be made of the same material in one form. The material of the binder that may be included in the first electrode active material layer 12 may be used as the material of the binder of the solid electrolyte layer.

[0113] The release film attached to the first surface of the solid electrolyte layer is not limited as long as the release film is highly adhesive. In addition, the release film is not particularly limited as long as the release film is easily removed from the solid electrolyte after the solid electrolyte layer is stacked on the first unit or the second unit, because the solid electrolyte is difficult to handle only due to the physical properties of the solid electrolyte. The release film may include one selected from the group consisting of polyethylene terephthalate (PET), polyimide (PI), polypropylene (PP), polyethylene (PE) and polycarbonate (PC).

[0114] In the preparation of the battery assembly ( S40 ), the first unit 10 , the second unit 20 , and the solid electrolyte layer 30 prepared above are stacked on one another.

[0115] The first unit and the second unit are alternately stacked by repeating the following steps: stacking one of the first unit and the second unit on the second surface of the solid electrolyte layer to which no release film is attached; removing the release film from the first surface of the solid electrolyte layer, and stacking the remaining one of the first unit and the second unit on the first surface of the solid electrolyte layer from which the release film is removed, wherein the remaining one is different from the one stacked on the second surface of the solid electrolyte layer.

[0116] Specifically, the first unit 10 or the second unit 20 is located in the central portion 31 of the second surface of the solid electrolyte layer 30 to which the release film is not attached. Therefore, the first electrode active material layer 12 or the second electrode active material layer 22 is stacked on and in contact with the solid electrolyte layer 30. Then, a unit different from the unit stacked on the second surface is located on the central portion 31 of the first surface, on which the release film of the solid electrolyte layer is removed so that the electrode active material layer of the unit located on the first surface is stacked on and in contact with the solid electrolyte layer 30. The above steps can be repeated to alternately stack the first unit, the second unit, and the solid electrolyte layer in a manner that the solid electrolyte layer is placed between the first unit and the second unit.

[0117] Here, the first unit 10 has an area equal to or larger than the second unit 20, and the central portion 31 of the solid electrolyte layer 30 has an area larger than the second unit 20. Figure 4 The distance x between the edge of the solid electrolyte layer and the edge of the first unit 1 or the distance x between the edge of the solid electrolyte layer and the edge of the second unit 2 It may be about 10 μm to 2000 μm. The thickness y of the solid electrolyte layer may be about 10 μm to 500 μm. In one form, the equation 1 may be satisfied: 2<log(x 1 y)<6 or equation 2: 2<log(x 2 y)<6. When log(x1 y) or log(x 2 When the value of log(x) is less than 2, the possibility of short circuit is high because the edge of the electrode may be exposed after the pressing process. 1 y) or log(x 2 When the value of y) is greater than 6, the energy density may be reduced due to providing an unnecessary amount of material in the all-solid-state battery. Fig. 6A and Figure 6B This can be confirmed. Fig. 6A As shown, in all-solid-state batteries, <log(x 1 In the case where 2<log(x)<6, the possibility of short circuit is high because the edge of the electrode may be exposed after the pressurization process. 1 In the case of an all-solid-state battery in the range of y) < 6, the solid electrolyte protects the edges of the electrodes during pressurization and prevents short circuits.

[0118] In addition, in the prior art, when each battery cell including a first electrode, a second electrode and a solid electrolyte is stacked on each other, the first electrode collectors are stacked on each other or the second electrode collectors are stacked on each other so that the two collectors are stacked on each other. As a result, since many collectors are used, it is difficult to obtain an all-solid-state battery with a high energy density. On the contrary, in the present disclosure, since a first electrode collector or a second electrode collector having a thickness of about 4 μm to 20 μm is provided between a pair of first electrode active material layers or a pair of second electrode active material layers, the number of layers is reduced compared to the process in the prior art, and the number of collectors is reduced. As a result, the process of manufacturing an all-solid-state battery can be simplified, and an all-solid-state battery with a high energy density can be obtained.

[0119] The first electrode unit, the second electrode unit, and the solid electrolyte layer may be stacked on each other and configured in a jelly roll structure or the like.

[0120] When pressurizing the battery assembly ( S50 ), the prepared battery assembly is pressurized to obtain an all-solid-state battery.

[0121] The method of pressurizing the battery assembly can be flat pressing, ultra-high pressure isostatic pressing, uniaxial pressing, cold isostatic pressing (CIP) or hot pressing. In one form, the pressurizing method can be flat pressing or ultra-high pressure isostatic pressing.

[0122] Traditionally, basic battery cells are individually pressurized and then stacked on top of each other. However, the present disclosure simplifies the process because the final battery assembly is prepared and then pressurized.

[0123] When a battery assembly stacked with five cells was pressurized to 200 MPa, failure occurred at the interface of the battery assembly. However, when the battery assembly was pressurized to 300 MPa, there was no failure at the interface. Therefore, in order to manufacture an all-solid-state battery in which the battery operates without failure, pressurization can be performed under conditions of 250 MPa to 500 MPa.

[0124] Hereinafter, the present disclosure will be described in more detail with reference to an exemplary form. This form is only an example of the present disclosure, and therefore it should be understood that the scope and spirit of the present disclosure are not limited thereto.

[0125] form

[0126] (S10) Copper (Cu), copper (Cu) coated with carbon (C), or nickel (Ni) is used as a negative electrode collector, and its thickness is about 5 μm to 15 μm, 7 μm to 20 μm, or 4 μm to 20 μm. A slurry for preparing a negative electrode active material layer is prepared by using a graphite-based negative electrode active material, a butyrate-based solvent, a sulfide-based solid electrolyte, and a rubber binder. A negative electrode active material layer is formed on the opposite surface of the negative electrode collector by a slurry coating method, thereby preparing a first unit. Here, the composite density of the negative electrode active material is about 0.5 g / cc to 3.0 g / cc.

[0127] (S20) Aluminum (Al) or aluminum (Al) coated with carbon (C) can be used as a positive electrode collector with a thickness of about 5 μm to 15 μm or 7 μm to 20 μm, respectively. A slurry for preparing a positive electrode active material layer is prepared by using a nickel cobalt manganese-based (NCM) positive electrode active material, a butyrate-based solvent, a sulfide-based solid electrolyte, and a rubber adhesive. A positive electrode active material layer is formed on the opposite surface of the positive electrode collector by a slurry coating method, thereby preparing a second unit. Here, the composite density of the positive electrode active material is about 0.1 g / cc to 2.0 g / cc.

[0128] (S30) A solid electrolyte layer is prepared using a sulfide-based solid electrolyte and a rubber adhesive. Then, a PI film is used as a release film and attached to a first surface of the solid electrolyte layer.

[0129] (S40) A battery assembly is obtained by stacking a first unit and a second unit. Specifically, the first unit 10 or the second unit 20 is placed in the central portion 31 of the second surface of the solid electrolyte layer 30 to which the release film is not attached. Therefore, the first electrode active material layer 12 or the second electrode active material layer 22 is stacked on and in contact with the solid electrolyte layer 30. Then, a unit different from the unit stacked on the second surface is placed on the central portion 31 of the first surface, on which the release film of the solid electrolyte layer is removed, so that the electrode active material layer of the unit located on the first surface is stacked on and in contact with the solid electrolyte layer. Repeat the above steps to alternately stack the first unit, the second unit, and the solid electrolyte layer in a manner that the solid electrolyte layer is placed between the first unit and the second unit.

[0130] (S50) The battery assembly is pressurized to reduce the thickness of the negative electrode active material layer and the positive electrode active material layer by 50 μm to 300 μm.

[0131] Experimental Example 1—Pressure Range Setting

[0132] In order to manufacture an all-solid-state battery according to one form of the present disclosure, experiments were conducted on the optimal pressurization range. Fig. 7A and Figure 7B Shown in.

[0133] Fig. 7A is a photograph of the interface of the intermediate layer between the second stacking unit and the third stacking unit after the battery assembly was pressurized to 200 MPa, and the battery assembly was prepared by alternately stacking the first unit and the second unit (including the solid electrolyte layer between the units) five times in one form. Figure 7B This is a photograph of the interface of the intermediate layer between the second stacking unit and the third stacking unit after the battery assembly is pressurized to 300 MPa. According to one form of the present invention, the battery assembly is prepared by alternating the stacking of the first unit and the second unit (including the solid electrolyte layer between the units) five times.

[0134] Reference Fig. 7A , confirmed that failure occurred at the interface of an all-solid-state battery manufactured by pressurizing the battery assembly to 200 MPa and represented only 70% of the actual battery performance. In contrast, reference Figure 7B , confirmed that the interface of the all-solid-state battery manufactured by pressurizing the battery assembly to 300MPa was free of failures and exhibited more than 95% of the actual battery performance.

[0135] As a result, in order to manufacture an all-solid-state battery that operates without trouble by the form of the present disclosure, it has been confirmed that for a battery assembly in which the first unit and the second unit are stacked five times, it is desirable to pressurize the battery assembly with 300 MPa or more.

[0136] Although the form of the present disclosure has been described with reference to the accompanying drawings, it will be appreciated by those skilled in the art that various modifications, additions and substitutions may be made without departing from the scope and spirit of the present disclosure. Therefore, the disclosed form of the present disclosure is for illustrative purposes only and should not be construed as limiting the present disclosure.

Claims

1. An all-solid-state battery, include: a plurality of first units, each of the plurality of first units comprising a first electrode current collector and a first electrode active material layer disposed on each opposing surface of the first electrode current collector; as well as a plurality of second units, each of the plurality of second units comprising a second electrode current collector and a second electrode active material layer disposed on each opposing surface of the second electrode current collector, wherein the first units in the plurality of first units and the second units in the plurality of second units are stacked alternately with each other; a plurality of solid electrolyte layers, wherein one of the plurality of solid electrolyte layers is disposed between a corresponding first unit among the plurality of first units and a corresponding second unit among the plurality of second units, and each of the plurality of solid electrolyte layers has an area larger than that of each of the plurality of first cells and equal to or larger than that of each of the plurality of second cells, Wherein, the all-solid-state battery is configured to satisfy the following equation 1 or equation 2: Equation 1:2 <log(x 1 y) < 6 Equation 2:2 <log(x 2 y) < 6 Among them, x 1 is the distance between the edge of the solid electrolyte layer and the edge of the corresponding first unit, x 2 is the distance between the edge of the solid electrolyte layer and the edge of the corresponding second unit, y is the thickness of the solid electrolyte layer, wherein the thickness y of the solid electrolyte layer is 10 μm to 500 μm, and Wherein, the distance x between the edge of the solid electrolyte layer and the edge of the corresponding first unit 1 , or the distance x between the edge of the solid electrolyte layer and the edge of the corresponding second unit 2 10μm to 2000μm.

2. The all-solid-state battery according to claim 1, in, The corresponding first unit has an area equal to or larger than that of the corresponding second unit, and wherein a central portion of the solid electrolyte layer has an area equal to or larger than that of the corresponding first unit or the corresponding second unit.

3. The all-solid-state battery according to claim 1, in, One of the corresponding first unit and the corresponding second unit is located on one surface of the solid electrolyte layer, and the remaining one of the corresponding first unit and the corresponding second unit, which is different from the unit located on the one surface, is located on the opposite surface of the solid electrolyte layer, so that the first electrode active material layer and the second electrode active material layer are stacked to contact the solid electrolyte layer.

4. The all-solid-state battery according to claim 1, in, An edge of the solid electrolyte layer and an edge of the corresponding first unit are parallel to each other, and An edge of the solid electrolyte layer and an edge of the corresponding second unit are parallel to each other.

5. The all-solid-state battery according to claim 1, in, The first electrode current collector of the corresponding first unit has a thickness of 4 μm to 20 μm, and the first electrode current collector is disposed between a pair of first electrode active material layers of the corresponding first unit, and The second electrode current collector of the corresponding second unit has a thickness of 5 μm to 20 μm, and is arranged between a pair of second electrode active material layers of the corresponding second unit.

6. The all-solid-state battery according to claim 1, in, The first electrode active material layer corresponding to the first unit has a thickness of 50 μm to 300 μm, a composite density of 1.2 g / cc to 3.5 g / cc, and a density of 10 mg / cm 2 Up to 45mg / cm 2 load level, and a brightness index of 30 to 80, and The second electrode active material layer corresponding to the second unit has a thickness of 50 μm to 300 μm, a composite density of 2.5 g / cc to 5.0 g / cc, and a 2 Up to 35mg / cm 2 load level, and a brightness index of 40 to 90.

7. A method for manufacturing an all-solid-state battery, the method The following steps are involved: preparing a plurality of first units, each of the plurality of first units comprising a first electrode current collector and a first electrode active material layer disposed on each opposing surface of the first electrode current collector; preparing a plurality of second units, each of the plurality of second units comprising a second electrode current collector and a second electrode active material layer disposed on each opposing surface of the second electrode current collector; preparing a battery assembly by alternately stacking first cells of the plurality of first cells and second cells of the plurality of second cells on each other; and applying pressure to the battery assembly, Wherein, preparing the battery assembly further comprises: A solid electrolyte layer is provided between a corresponding first unit of the plurality of first units and a corresponding second unit of the plurality of second units, wherein the solid electrolyte layer has a release film on a first surface thereof, and wherein the solid electrolyte layer has an area greater than that of any one of the plurality of first units and each of the plurality of second units, Wherein, the solid electrolyte layer, the corresponding first unit and the corresponding second unit are arranged to satisfy Equation 1 or Equation 2: Equation 1:2 <log(x 1 y) < 6 Equation 2:2 <log(x 2 y) < 6 Among them, x 1 is the distance between the edge of the solid electrolyte layer and the edge of the corresponding first unit, x 2 is the distance between the edge of the solid electrolyte layer and the edge of the corresponding second unit, y is the thickness of the solid electrolyte layer, wherein the thickness y of the solid electrolyte layer is 10 μm to 500 μm, and Wherein, the distance x between the edge of the solid electrolyte layer and the edge of the corresponding first unit 1 , or the distance x between the edge of the solid electrolyte layer and the edge of the corresponding second unit 2 10μm to 2000μm.

8. The method according to claim 7, in, Arranging the solid electrolyte layer comprises: stacking one of the corresponding first unit and the corresponding second unit on the second surface of the solid electrolyte layer to which the release film is not attached; removing the release film from the first surface of the solid electrolyte layer; and The remaining units of the corresponding first unit and the corresponding second unit are stacked on the first surface from which the release film is removed.

9. The method according to claim 7, in, An edge of the solid electrolyte layer and an edge of the corresponding first unit are parallel to each other, and An edge of the solid electrolyte layer and an edge of the corresponding second unit are parallel to each other.

10. The method according to claim 7, in, The pressurization is performed at 250 MPa to 500 MPa, and Wherein, when preparing the corresponding first unit and the corresponding second unit, the corresponding first unit and the corresponding second unit are not pressurized.